2017
DOI: 10.1021/acs.macromol.6b02400
|View full text |Cite
|
Sign up to set email alerts
|

Anthracene-Based Thiol–Ene Networks with Thermo-Degradable and Photo-Reversible Properties

Abstract: Reversible networks based on an alkenefunctionalized dimer of 9-anthracenemethanol were synthesized by photoinitiated radical thiol−ene polyaddition, using either a poly(dimethylsiloxane-co-propylmercaptomethylsiloxane) or a novel aliphatic trithiol synthesized from 1,2,4trivinylcyclohexane in a simple two-step procedure. The obtained networks were analyzed using differential scanning calorimetry, dynamic mechanical analysis, polarization microscopy, X-ray diffraction, and (photo)rheology. The two types of net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 22 publications
2
73
0
Order By: Relevance
“…It is reported that the rate of this dissociation, which is caused by anthracene dimers that dissociate cleanly at the elevated temperatures through a diradical transition state, depends on the substituents on the anthracene ring. 32 As expected, PAPMS-2 could be easily depolymerized than PAPMS-1 because the anthracene in PAPMS-2 was linked to an electron-withdrawing group. Sunlight is a green energy source, which includes light of various wavelengths; when it comes to the application in chemistry, sunlight is primarily used in the eld of photocatalysis.…”
Section: Resultssupporting
confidence: 51%
“…It is reported that the rate of this dissociation, which is caused by anthracene dimers that dissociate cleanly at the elevated temperatures through a diradical transition state, depends on the substituents on the anthracene ring. 32 As expected, PAPMS-2 could be easily depolymerized than PAPMS-1 because the anthracene in PAPMS-2 was linked to an electron-withdrawing group. Sunlight is a green energy source, which includes light of various wavelengths; when it comes to the application in chemistry, sunlight is primarily used in the eld of photocatalysis.…”
Section: Resultssupporting
confidence: 51%
“…Therefore, this thiol was not suited for unambiguous design of dynamic materials that are solely relying on dynamic thiol exchange. Hence, an aliphatic trifunctional thiol (trithiol) was synthesized and used as a reference building block to produce dynamic polymer materials.…”
Section: Resultsmentioning
confidence: 99%
“…The photocycloaddition, or photodimerization, of anthracene has been well‐known for a long time . Recently, it has experienced a renaissance as it has been used in a variety of material applications, including self‐healing materials, single‐chain nanoparticles, and in the formation of completely degradable networks . One reason anthracene was employed in the current resist, is the fact that it has been shown recently that the photodimerization of certain anthracene systems can be triggered in the visible light regime .…”
Section: Methodsmentioning
confidence: 99%